Mycoplasma hominis and Mycoplasma genitalium in the Vaginal Microbiota and Persistent High-Risk Human Papillomavirus Infection - Adebamowo, Sally N.; Ma, Bing; Zella, Davide; Famooto, Ayotunde; Ravel, Jacques; Adebamowo, Clement, ACCME Research Group (Frontiers in Public Health, 2017)
Background: Recent studies have suggested that the vaginal microenvironment plays a role in persistence of high-risk human papillomavirus (hrHPV) infection and thus cervical carcinogenesis. Furthermore, it has been shown that some mycoplasmas are efficient methylators and may facilitate carcinogenesis through methylation of hrHPV and cervical somatic cells. We examined associations between prevalence and persistence of Mycoplasma spp. in the vaginal microbiota, and prevalent as well as persistent hrHPV infections. Methods: We examined 194 Nigerian women who were tested for hrHPV infection using SPF25/LiPA10 and we identified M. genitalium and M. hominis in their vaginal microbiota established by sequencing the V3-V4 hypervariable regions of the 16S rRNA gene. We defined the prevalence of M. genitalium, M. hominis and hrHPV based on positive result of baseline tests while persistence was defined as positive results from two consecutive tests. We used exact logistic regression models to estimate associations between Mycoplasma spp. and hrHPV infections. Results: The mean (SD) age of the study participants was 38 (8) years, 71% were HIV positive, 30% M. genitalium positive, 45% M. hominis positive and 40% hrHPV positive at baseline. At follow up, 16% of the women remained positive for M. genitalium, 30% for M. hominis and 31% for hrHPV. There was a significant association between persistent M. hominis and persistent hrHPV (OR 8.78, 95% CI 1.49 - 51.6, p 0.01). Women who were positive for HIV and had persistent M. hominis had 3-fold increase in the odds of having persistent hrHPV infection (OR 3.28, 95% CI 1.31 - 8.74, p 0.008), compared to women who were negative for both. Conclusions: We found significant association between persistent M. hominis in the vaginal microbiota and persistent hrHPV in this study but we could not rule out reverse causation. Our findings need to be replicated in larger, longitudinal studies and if confirmed, could have important diagnostic and therapeutic implications.